Study of non-linear wave propagation phenomena in gas dynamics - Srivastava, Shobhit kumar (IIT(BHU) Varanasi, 2022)
Abstract is available in the attachment.
This thesis is submitted by Shobit Kumar Srivastava Department of Mathematical Sciences of IIT(BHU),Varanasi under the supervision of Dr. L.P. Singh.
Keywords: dynamics; phenomena; non-linear; wave; propagation